1 ppm-detectable hydrogen gas sensor based on nanostructured polyaniline - Perizat Askar; Dana Kanzhigitova; Aigerim Ospanova; Aslan Tapkharov; Sagydat Duisenbekov; Munziya Abutalip; Baktiyar Soltabayev; Amanzhol Turlybekuly; Salimgerey Adilov; Nurxat Nuraje (Scientific Reports)
Abstract The hydrogen (H2) energy industry has continued to expand in recent years due to the decarbonization of the global energy system and the drive towards sustainable development. Due to hydrogen’s high flammability and significant safety risks, the efficient detection of hydrogen has become an increasingly hot issue today. In this work, a new type of relatively fast and responsive conducting polymer sensor has been demonstrated for tracing H2 gas in a nitrogen environment. Inspiration of unique properties of carbon nanotube (CNT) and graphene, polyaniline (PANI) hollow nanotubes, PANI thin films are fabricated to study for structural-properties investigation. The PANI hollow nanotube sensor ensures the 1 ppm hydrogen gas detection at room temperature, and exhibits high sensitivity (29%) and fast response and recovery times of 15 and 17 s, follows by PANI thin film sensor (20%), response and recovery times of 65s and 45s. This conducting polymer-based hydrogen sensor holds promise for the early detection of H2 leaks in a wide range of industries.